Pengembangan Training Kit Solar Tracker Berbasis Arduino untuk Meningkatkan Kreativitas dan Motivasi Belajar Peserta Didik - Achmad Yogi Pramana; Joko Joko; Tri Rijanto; Yulia Fransisca (Indo Publishing, 2026)
The limited interactive learning media regarding renewable energy in vocational schools has an impact on the low creativity and learning motivation of students. This study aims to develop a feasible, practical, and effective Arduino-based Solar Tracker Training Kit. Using the ADDIE model Research and Development (R&D) method, this research was conducted at SMKN 3 Jombang with 36 subjects of grade XI Industrial Electronics Engineering through a one-group pre-test post-test design. Data were collected through observation, interviews, questionnaires, and tests using validation sheet instruments, response surveys, and evaluation questions. Data analysis applied descriptive statistics percentages, N-Gain tests, and Wilcoxon tests because the data were not normally distributed (< 0.05). The results showed that the product was